The Effect Of Progressive Muscle Relaxation On Sleep Quality In Patients With Hypertension In South Cilacap City - KASRON KASRON; SUSILAWATI SUSILAWATI (NURSCOPE: Jurnal Penelitian dan Pemikiran Ilmiah Keperawatan, 2017)
Introduction : Patients with hypertension patients can have sleep disorders such as dizziness or headache, feeling tired during the day, anxiety, decreasing concentration and irritability. This study aimed to evaluate the effect of progressive muscle relaxation (PMR) on sleep quality in patients with hypertension in South Cilacap City. Method : The research used quasi-experiment with pre-post test without control group. Respondents werw patients with hypertension in South Cilacap City, with the criteria forthose who were active in health care programme, able to perform independent activities, consume of anti-hypertensive drugs, have done PMR regularly for 7 days, and the exclusion criteria was patients with impaired osteoarthritis and rheumatoid arthritis. Pittsburgh Sleep Quality Index (PSQI) was used to evaluate sleep quality twice, before and 7 days after interventions PMR. Statistic analysis used wilcoxon test. 16 respondents included in the criteria. Result : The quality of sleep before treatment PMR was 7 people (43.8%) poor, 9 people (56.3%) very bad. After treatment PMR was 3 people (18.8%) rather good, 13 people (81.3%) less good. The analysis shown the sleep quality was difference between before and after PMR with p-value <0.001. Discussion : The study shows there is difference between before and after PMR in hypertensive patients in South Cilacap. PMR can be used to improve the sleep quality of hypertensive patients.